The role of energy infrastructure in shaping early adoption of electric and gasoline cars - Taalbi, Josef; Nielsen, Hana (Lund University, 2021)
Electric vehicles have a potential to lower greenhouse gas emissions but still face challenges. This study asks what can be learned from US automobile history. In 1900 there were three equal contenders in the US automotive industry: gasoline, electric and steam cars. Only a decade later the gasoline car had achieved a crushing dominance. This dominance is often attributed to techno-economic factors, such as an innate inferiority of electric cars. Meanwhile, the role of infrastructures is not well understood. The research project examines the mechanisms behind this process, using information on more than 36,000 passenger car models. One result is that the slow diffusion of electricity infrastructure gave gasoline cars the upper hand.

Elbilar har potential att sänka utsläpp av växthusgaser men står fortfarande inför utmaningar. Denna databas innehåller detaljerad information om amerikanska bilmodeller, inklusive el- och ångbilar, och möjliggör studium av historiska teknikval. År 1900 fanns det tre jämbördiga konkurrenter i den amerikanska fordonsindustrin: bensin-, el- och ångbilar. Bara ett decennium senare hade bensinbilen erövrat marknaden. Denna dominans tillskrivs ofta tekno-ekonomiska faktorer, såsom en inneboende underlägsenhet hos elbilar. Forskningsprojektet undersöker mekanismerna bakom denna process, med hjälp av information om mer än 36 000 personbilsmodeller. Ett resultat är att den långsamma utvecklingen av elinfrastruktur gav bensinbilarna överhanden.
Infrastrukturens betydelse för den historiska utvecklingen av elbilar och bensinbilar - The role of energy infrastructure in shaping early adoption of electric and gasoline cars
Keywords: Electric cars; Elbilar; Gasoline cars; Bensinbilar; technology choice; teknikval; infrastructure; infrastruktur; SCIENCE AND TECHNOLOGY; VETENSKAP OCH TEKNOLOGI; SOCIETY AND CULTURE; SAMHÄLLE OCH KULTUR; HISTORY; HISTORIA; Economic History; Ekonomisk historia